Spiritual dominant and ageing of organism - V. D. Troshin (Бюллетень сибирской медицины)
The paper shows conception of integrative ageing of organism based upon complex approach and clinical-and-psychological, clinical-and-neurophysiological and neuroimmunological studies. Spiritual-and-psychic and genomic spheres of activity play major role in ageing and combine nervous, endocrine and immune systems. Controlling systems take part in pathological process that’s why there have to be integrative attitude with accent on spiritual-and-psychic and genomic spheres. Spiritual dominant in man’s life is the basis of health harmony and active longevity.